Combination prediction and error analysis of conventional gas production in Sichuan Basin - Li, Haitao; Yu, Guo; Chen, Yanru; Fang, Yizhu; Chen, Yu; Zhang, Dongming (Frontiers in Earth Science, 2023)
The accurate prediction of the trend of natural gas production changes plays an important role in the formulation of development planning plans. The conventional gas exploration and development in Sichuan Basin has a long history. According to the development of conventional gas production, the Hubbert model, Gauss model and GM(1, N) model are used to predict the conventional gas production respectively, and then the Shapley value method is used to allocate the weight values of the three models, and a combination model for conventional gas production prediction is established. Finally, residual analysis and precision test are carried out on the prediction results. The results show that: (1) The combination model established using the Shapley value method can effectively combine the advantages of various models and improve the accuracy of prediction. And the standardized residual of the combined model is the lowest, the prediction is closest to the actual value, and the accuracy test is the best, indicating that the combined model has the highest accuracy and the method is the most reliable. (2) After using a combination model for prediction, conventional gas production will peak in 2046, with a peak production of 412 × 10 8 m 3 , with a stable production period of (2038-2054) years, a stable production period of 17 years, and a stable production period of 389× 10 8 m 3 , the predicted results of the combined model have a longer stable production period, and the trend of production changes is more stable.